A Nietzschean tafsīr for Nazi Germany: The Commentary to Sadr-ud-Dīn’s Qur’an of 1939 - Jonker, Gerdientje (Journal of Qur'anic Studies, 2024)
This contribution traces the history of the German Qur'an edition published by the Ahmadiyya Anjuman Isha’at-e-Islam Lahore (Lahore-Ahmadiyya) in Berlin in 1939. Maulvi Sadr-ud-Dīn, the Lahore-Ahmadiyya missionary who erected the first mosque in Berlin, fashioned the translation. To reach out to a German audience gearing up for war, he entrusted his Berlin collaborator, the philosopher Hugo Marcus, with the details of the commentary. The narrative starts in 1924, when Tatar intellectuals first sat down with Sadr-ud-Dīn to discuss the necessity of preparing Qur'an editions for European readers. It ends with the publication of the German Qur'an at the moment Germans were finalising their war preparations. Hugo Marcus’ approach to his commentary involved relating single Qur'an verses to Friedrich Nietzsche's philosophy, focusing on genius, heroism, and suffering. In making that choice, he connected the Qur'anic text to the Herrenethik (‘ethics of male superiority’) that pervaded National-Socialist (Nazi) ideology. From this emerged an exegesis full of delusions about masculinity and racist arrogance. A comparison with Hugo Marcus’ writings of the 1930s illustrates how it was wrought. In their approach to racism, nationalism, and war, Ahmadi Muslim missionaries and German Muslims in Berlin differed considerably. In their many attempts to bridge East and West through religion, their disagreements on these issues present a pivotal moment in intercultural communication, leaving an imprint on how the Qur'an was explained in Sadr-ud-Dīn's translation. Whereas the Lahore-Ahmadiyya tried to smooth the way towards an ‘international religion’ and defended the ‘Jihad of the Pen’, German Muslims steered close to the expectations of a frenzied, war-minded public. A straightforward document, Hugo Marcus’ tafsīr served to exonerate them in advance, wherever they were heading.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Friedrich Nietzsche; Hugo Marcus; Lahore-Ahmadiyya; Nazi Germany; rationalist Islam; Sadr-ud-Dīn; tadjdīd; Tatar Reformers

Die vergessene Geschichte des Islam in Bayern - Jonker, Gerdientje; Nowar, Nina; Müssig, Stephanie (2018)

Introduction - Jonker, Gerdientje; Müssig, Stephanie (Journal of Muslims in Europe, 2022)

Turkish Mosque Archives in Industrial Towns in Southern Germany: An Ethnographic Survey - Jonker, Gerdientje; Elbel, Isabel; Klein, Arne; Klopke, Jule; Müssig, Stephanie; Schönstedt, Jens; Ulbricht, Victoria (Journal of Muslims in Europe, 2022)
Starting from the thesis that European mosque archives offer important sources for the history of Muslims and Islam in Europe, this contribution presents results of a pilot survey into the whereabouts of mosque archives in Germany. Focusing on five small towns in industrial zones where predominantly Turkish contract workers have settled, we asked Turkish mosque administrators, chairmen and imams how they had handled papers in the past, whether and where they had stored folders that were not in use anymore, and what kind of documents their collections contained. What we found were various archival records in a wide and unexpected range of places. We also learned that our questions prompted very different reactions. Umbrella organisations understood their archives as tools for preserving the written sources documenting their origins, whereas local administrators tended to see them as records of their personal memories. Our conclusion is that the time is ripe for the development of knowledge about mosque archives in Germany and, with regard to the founding generation, this is of crucial importance.
Created from Fastlane, Scopus look-up
Keywords: ethnographic survey; Germany; history of Muslims; mosque archives